Unique antibodies across the animal kingdom (birds, camelids, and sharks): therapeutic potential against human respiratory viral infections - Basabrain, Ammar A.; Alandijany, Thamir A. (Frontiers in Immunology, 2025)
Antibodies represent indispensable tools in the armamentarium against infectious diseases, with widespread application in prophylactic, therapeutic, and diagnostic settings. Conventional mammalian immunoglobulin G (IgG) antibodies have been extensively utilized in clinical and research contexts; however, their utility is sometimes constrained by intrinsic limitations such as thermal instability, susceptibility to proteolytic degradation, limited mucosal efficacy, and the high costs associated with mammalian expression systems. These challenges have driven increasing interest in alternative antibody formats derived from non-mammalian species that offer distinct structural and functional advantages. In recent years, a growing body of research has focused on non-canonical immunoglobulins, including immunoglobulin Y (IgY) from birds, nanobodies derived from the variable domain of heavy-chain-only antibodies (VHH) in camelids, and variable new antigen receptors (VNARs) sourced from the immunoglobulin new antigen receptor (IgNAR) system in cartilaginous fish such as sharks. The structural simplicity and functional robustness of these antibody platforms enable their integration into diverse biomedical applications, encompassing passive immunization, targeted drug delivery, and point-of-care diagnostics. Indeed, these molecules exhibit unique biochemical properties, including superior thermal and protease resistance, small molecular size, and the ability to access recessed or conformational epitopes that are often inaccessible to conventional IgG antibodies. Moreover, their typically lower immunogenic profiles and reduced pro-inflammatory activity render them suitable for a broad range of therapeutic strategies, including repeated administration and mucosal delivery, and position them as particularly promising agents for combating respiratory pathogens. This review highlights the unique properties, practical advantages, and translational therapeutic potential of IgY, nanobodies, and VNARs. It underscores their advantages over traditional antibody formats and their emerging role as next-generation Immunotherapeutics in the global effort to address persistent and emerging respiratory viral threats.